A fully-automated low-cost cardiac monolayer optical mapping robot - Lee, Peter; Hou, Luqia; Alibhai, Faisal J.; Al-attar, Rasha; Simón-Chica, Ana; Redondo-Rodríguez, Andrés; Nie, Yilin; Mirotsou, Maria; Laflamme, Michael A.; Swaminath, Gayathri; Filgueiras-Rama, David (Frontiers in Cardiovascular Medicine, 2023)
Scalable and high-throughput electrophysiological measurement systems are necessary to accelerate the elucidation of cardiac diseases in drug development. Optical mapping is the primary method of simultaneously measuring several key electrophysiological parameters, such as action potentials, intracellular free calcium and conduction velocity, at high spatiotemporal resolution. This tool has been applied to isolated whole-hearts, whole-hearts in-vivo, tissue-slices and cardiac monolayers/tissue-constructs. Although optical mapping of all of these substrates have contributed to our understanding of ion-channels and fibrillation dynamics, cardiac monolayers/tissue-constructs are scalable macroscopic substrates that are particularly amenable to high-throughput interrogation. Here, we describe and validate a scalable and fully-automated monolayer optical mapping robot that requires no human intervention and with reasonable costs. As a proof-of-principle demonstration, we performed parallelized macroscopic optical mapping of calcium dynamics in the well-established neonatal-rat-ventricular-myocyte monolayer plated on standard 35 mm dishes. Given the advancements in regenerative and personalized medicine, we also performed parallelized macroscopic optical mapping of voltage dynamics in human pluripotent stem cell-derived cardiomyocyte monolayers using a genetically encoded voltage indictor and a commonly-used voltage sensitive dye to demonstrate the versatility of our system.